2015
DOI: 10.1021/acs.biomac.5b00678
|View full text |Cite
|
Sign up to set email alerts
|

Holocellulose Nanofibers of High Molar Mass and Small Diameter for High-Strength Nanopaper

Abstract: Wood cellulose nanofibers (CNFs) based on bleached pulp are different from the cellulose microfibrils in the plant cell wall in terms of larger diameter, lower cellulose molar mass, and modified cellulose topochemistry. Also, CNF isolation often requires high-energy mechanical disintegration. Here, a new type of CNFs is reported based on a mild peracetic acid delignification process for spruce and aspen fibers, followed by low-energy mechanical disintegration. Resulting CNFs are characterized with respect to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 38 publications
7
75
0
Order By: Relevance
“…The tensile strength and elastic modulus of the non-alkaline treated HCNF nanopaper were 155 to 178 MPa and 3.9 to 4.4 GPa, respectively, which is higher than the tensile properties of the PCNF with tensile strength of 59 to 67 MPa and elastic modulus of 1.7 to 1.9 GPa. Galland et al (2015) reported an improvement in the tensile strength and elastic modulus of nanopaper with higher hemicellulose content. They explained this phenomenon in terms of the better packing effect due to hemicellulosecoated cellulose in individual HCNFs.…”
Section: Fig 1 Sem Images Of Hcnfs With Different Hemicellulose Conmentioning
confidence: 95%
See 1 more Smart Citation
“…The tensile strength and elastic modulus of the non-alkaline treated HCNF nanopaper were 155 to 178 MPa and 3.9 to 4.4 GPa, respectively, which is higher than the tensile properties of the PCNF with tensile strength of 59 to 67 MPa and elastic modulus of 1.7 to 1.9 GPa. Galland et al (2015) reported an improvement in the tensile strength and elastic modulus of nanopaper with higher hemicellulose content. They explained this phenomenon in terms of the better packing effect due to hemicellulosecoated cellulose in individual HCNFs.…”
Section: Fig 1 Sem Images Of Hcnfs With Different Hemicellulose Conmentioning
confidence: 95%
“…Iwamoto et al (2008) reported that the amount of hemicellulose in pulp affects the ease of defibrillation and the properties of the produced paper sheets. Galland et al (2015) prepared holocellulose nanofibers (HCNFs) using the acid chlorite method for delignification, reporting that the content of hemicellulose in HCNF influenced the properties of the nanopaper sheets. The obtained HCNFs are unique in terms of their high molecular weight and cellulose-hemicellulose core-shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of chemical composition, cellulose nanofibrils (CNF) can be classified as lignocellulose nanofibrils (LCNF) that contain both lignin and hemicellulose, holocellulose nanofibrils (HCNF) that contain only hemicellulose and no lignin, and pure cellulose nanofibrils (PCNF) that contain only the cellulose component (Lee et al 2010;Kumagai et al 2013;Galland et al 2015). The diameter of LCNF generally ranges from the submicron scale up to 15 nm, which is larger than the average diameters of HCNF and PCNF (Jang et al 2013;Park et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the disruption and loosening of the cell wall structure by delignification (Iwamoto et al 2008;Park et al 2015). The HCNF has a core-shell structure in which the hemicellulose shell surrounds a cellulose core (Wan et al 2010;Galland et al 2015). The presence of hemicellulose is known to improve the mechanical properties of HCNF nanopapers and nanocomposites (Galland et al 2015;Prakobna et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation